Pengaruh Relationship Marketing dan Kepercayaan Konsumen terhadap Keputusan Pembelian pada Master Printing Kabupaten Mamuju - Muh. Aldyanto Nur; Muhammad Arysad; Ratna (Jurnal Ragam Pengabdian, 2026)
This study aims to examine the effect of relationship marketing and consumer trust on purchasing decisions at Master Printing, Mamuju Regency. This research employed a quantitative approach with an associative research design. The research sample consisted of 100 respondents, determined using the Lemeshow formula with a convenience sampling technique. Data were collected through observation, interviews, documentation, and questionnaires, and were analyzed using validity and reliability tests, multiple linear regression analysis, partial tests (t-test), simultaneous tests (F-test), and the coefficient of determination. The results indicate that relationship marketing and consumer trust each have a positive and significant effect on purchasing decisions. Furthermore, both variables simultaneously exert a significant influence on purchasing decisions, with a coefficient of determination of 0.500, indicating that 50% of the variation in purchasing decisions can be explained by relationship marketing and consumer trust, while the remaining percentage is influenced by other variables outside the research model. These findings confirm that strengthening customer relationships and enhancing consumer trust play a strategic role in encouraging purchasing decisions in the printing service business at Master Printing, Mamuju Regency.